THE ROLE OF THE SERBIAN ORTHODOX CHURCH IN THE PROTECTION OF NATIONAL INTERESTS IN KOSOVO AND METOHIA FROM 1945 TO 1999 (Heritage, 2022)
In this paper, we consider the period from 1945 to 1999. First, because we believe that this period was extremely turbulent, both for the survival of the Serbian people and for the survival of the Serbian Orthodox Church. We believe that there are few works that have observed this period from the aspect of the church's point of view. Guided by the books of the Bishop of Raško-Prizren, the retired Patriarch Pavle, Metropolitan Amfilohi Radović and Bishop Atanasi Jeftić, in our work we aim to prove from the church aspect (according to church documents) that the extermination of the Serbian people has continued continuously since 1945, that it was carefully conceived and executed. Parallel to the exodus of the Serbian people, there was also an exodus of the Serbian Orthodox Church, which essentially never left the Serbian people in Kosovo and Metohija and is still with them today.
Keywords: Kosovo and Metohija, Bishop Pavle of Raško-Prizren, Metropolitan Amfilohije Radović, Bishop Atanasije Jevtić, persecution of the Serbian people